سيناريو افتراضي بأستخدام الأقمار الاصطناعية لاعمال الموانئ العراقية (مجلة المنصور, 2023)
The maritime work requires a lot of requirements, which reflected the ambiguity that surrounds the aids reliable in cases of embarrassment and danger that characterized workers in this field to challenge the difficulties they face, whatever the practice and depth of experience as always expect a sudden and urgent.Specialists have been working in this area on the production and manufacturing all necessary equipment and devices that bear the most severe maritime and weather conditions to enable the maritime face potential difficulties, and the most important tools that help to create suitable conditions are a means of maritime communications, which has the active role in identifying the location and weather forecasts identify the route and access to appropriate information relating to flights and the launch of the marine warnings and ask for help and supplies distress. And achieve clear communication on different levels and patterns consistent with the standard specifications contained in the instructions of International Maritime Organization and the IMO Convention on the Safety of Life at Sea SOLAS and the World Telecommunication ITU, where the work is helpful in redressing the risks and request aid when needed and to avoid sailing in dangerous areas, collisions and to ensure the necessary information,The most important means in this area is the means of communication via satellite, hence the role of the INMARSAT that Iraq was co-founder in 1976 of Iraq where the introduction of GMDSS for the special conditions in order to enhance the port authority and to maximize resources and enhance the reputation of Iraqi ports and service delivery applicants to the standard specifications to save lives, the environment and property.